PENERAPAN MODEL PEMBELAJARAN TTA (TIME TOKEN ARENDS) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA JERMAN PADA SISWA KELAS XI IPA 7 SMA NEGERI 16 SURABAYA - RINI M, SETYO (LATERNE, 2013)
Speaking skills is one of the four language skills should be mastered by students. But the fact is, there are manystudents still having difficulty in speaking. Therefore, it is necessary to apply a variety of learning model models in orderto achieve competence in language learning, especially in speaking skills. One of learning that can be applied is themodel Time Token Arends. Problem of this research is (1) How does the application of the TTA (Time Token Arends) inGerman language speaking skills learning class XI Science 7 SMAN 16 Surabaya? (2) Is there an increase in studentlearning outcomes class XI Science 7 SMAN 16 Surabaya in speaking skills as applied learning model TTA (TimeToken Arends)? This research is a descriptive study using a qualitative approach. The data used in this study is theobservation sheets and tests. From the results of the study indicated that: (1) The application of the model TTA (TimeToken Arends) effectively used in speaking skills because it can optimize the learning process so that learning activitiesare not boring and that can cultivate students to be more interest in learning. From the results of the observation sheetindicated the overall frequency of student activities, including criteria and 88.3% very good. (2) There is an increase inthe student learning outcomes class XI Science 7 SMAN 16 Surabaya in German language speaking skills as appliedlearning model TTA (Time Token Arends). From the comparison of pre-test and post-test indicated an average pre-test of58.33 and the average post-test of 84.84.Keywords : Learning Model, Speaking skill, TTA (Time Token Arends)